FINANCIAL SYSTEM CREDITS TO THE PRIVATE SECTOR AND CREDIT MARKET REGULATION IN PERU - Rodriguez Cairo, Vladimir (2017)
The objective of the research is to explain why the freedom in the credit market positively affects the loans of the financial system to the private sector in Peru, generating an increase in the stock of loans to the private sector. Based on this objective, a descriptive and inferential analysis was performed on the relationship between the variables. Thus, the main results were that the freedom in the market of credits as a component of the regulation of the market of credits, influenced in the stock of credits of the financial system to the private sector of the country. In this way, it was concluded that the freedom in the credit market favors the stock of credits and, consequently, contributes to deepening the financial system. However, greater freedom in the credit market is an essential aspect of increasing credits to the private sector, but it is not the only element.